A sensor array based on planar electromagnetic sensors for agro-environmental monitoring - Mohamad @ Abd. Rahman, Syahrul Hisham (2013)
Agriculture is one of the important sectors in the country however due to lack of management and knowledge, farmers usually ended up overusing pesticide and fertilizers which can cause negative effects to the environment. Based on this situation monitoring of the agro-environment is important in order to maintain the permanence of the soils. As to date, available methods for contaminations detection in agriculture soils commonly require tedious operational procedures which usually involve purchase expensive equipments. This project suggests an alternative method for the detection of contamination by developing a sensor array with the combination of planar meander and interdigital electromagnetic sensors for monitoring the content in agricultural soils and contamination. The main objective is to fabricate the sensor array using printed circuit board (PCB). For this project three new configuration of planar electromagnetic placement re introduced which are parallel, wye and delta. An experimental setup consists of frequency waveform generator, signal oscilloscope and Agilent software as the controller was developed to study on the output of the system. A set of experiments were conducted to determine the relationship between the sensor’s output and the soil’s parameters. The performance of the system was observed where the sensors were tested with soil samples taken with different concentration of water percentage. Based on the result, the sensor array can be expected to be used to measure the contamination in the soils and the data accuracy is compared.